Prevalence of Selected Non-Metric Dental Traits in Indo-Nepalese and Tibeto-Nepalese Ethnic Groups of Western Hilly Region - Sah, Sanjay Kumar (JNMA J Nepal Med Assoc, 2019)
INTRODUCTION: Additional anatomic features present on teeth are called non-metric dental traits. Carabelli’s cusp and shovelling are such traits which are mostly evaluated for identification of ethnicity. The present study aims to determine the prevalence of Carabelli’s cusp and shovelling among Indo-Nepalese and Tibeto-Nepalese ethnic group. METHODS: A descriptive cross-sectional study was conducted in a tertiary hospital from March 22 to June 22 2019 after obtaining ethical approval from the institutional review committee. The study was conducted among 274 patients and convenient sampling method was applied. Data were analyzed by the help of Statistical Package for Social Sciences version 21. RESULTS: Among 274 cases, 153 (55.84%) cases were Indo-Nepalese and 121 (44.16%) were Tibeto-Nepalese. Carabelli’s cusp (16/26) was noticed in 87 (56.86%) of Indo-Nepalese and 45 (37.19%) of Tibeto-Nepalese. Shovelling (11, 12, 21, 22) was present in 47 (30.71%) Indo-Nepalese and 79 (65.28%) of Tibeto-Nepalese. Further, Carabelli’s cusp (16/26) was found in 77 (53.10%) females and 55 (55.12%) males. Shovelling was present in 75 (51.72%) females and 51 (39.53%) males. Bilateralism with respect to Carabelli’s cusp was present in 82 (62.2%) cases. Presence of bilateral shovelling on upper central incisors and lateral central incisors were among 117 (94.35%) and 56 (91.80%) respectively. CONCLUSIONS: Carabelli’s cusps are frequently found in Indo-Nepalese ethnic group and shovelling of teeth most commonly present in Tibeto-Nepalese population. Further, bilaterism for shovelling of teeth is more common than bilaterism for cusp of Carabelli.